2018
DOI: 10.1002/anie.201801894
|View full text |Cite
|
Sign up to set email alerts
|

Palladium/Norbornene‐Catalyzed C−H Alkylation/Alkyne Insertion/Indole Dearomatization Domino Reaction: Assembly of Spiroindolenine‐Containing Pentacyclic Frameworks

Abstract: Reported is a highly chemoselective intermolecular annulation of indole-based biaryls with bromoalkyl alkynes by using palladium/norbornene (Pd/NBE) cooperative catalysis. This reaction is realized through a sequence of Catellani-type C-H alkylation, alkyne insertion, and indole dearomatization, by forming two C(sp )-C(sp ) and one C(sp )-C(sp ) bonds in a single chemical operation, thus providing a diverse range of pentacyclic molecules, containing a spiroindolenine fragment, in good yields with excellent fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 84 publications
(4 reference statements)
0
42
0
1
Order By: Relevance
“…In a similar manner, the domino process exploiting 1‐(2‐iodobenzyl)‐1 H ‐pyrrole and ‐indoles as the reaction partners afforded a series of seven‐membered‐ring fused heterocycles 83 (Scheme b) and 84 (Scheme c) in moderate to high yields . Recently, the group of Luan reported an elegant domino reaction between 3‐(2‐iodophenyl)‐1 H ‐indoles and tethered bromoalkyl alkynes for the concise assembly of pentacyclic products 85 , which contained an interesting spiroindolenine motif (Scheme d) . In addition, the group of Lautens discovered that, in the absence of an adjacent heteroaryl or benzyl group on aryl iodide substrates, vinylpalladium species 81 underwent further carbopalladation of NBE to afford sterically crowded tetrasubstituted helical alkenes 86 through C−H functionalization on the adjacent aromatic ring (Scheme e) .…”
Section: Multifunctional Alkylating Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar manner, the domino process exploiting 1‐(2‐iodobenzyl)‐1 H ‐pyrrole and ‐indoles as the reaction partners afforded a series of seven‐membered‐ring fused heterocycles 83 (Scheme b) and 84 (Scheme c) in moderate to high yields . Recently, the group of Luan reported an elegant domino reaction between 3‐(2‐iodophenyl)‐1 H ‐indoles and tethered bromoalkyl alkynes for the concise assembly of pentacyclic products 85 , which contained an interesting spiroindolenine motif (Scheme d) . In addition, the group of Lautens discovered that, in the absence of an adjacent heteroaryl or benzyl group on aryl iodide substrates, vinylpalladium species 81 underwent further carbopalladation of NBE to afford sterically crowded tetrasubstituted helical alkenes 86 through C−H functionalization on the adjacent aromatic ring (Scheme e) .…”
Section: Multifunctional Alkylating Reagentsmentioning
confidence: 99%
“…[53] Recently, the group of Luan reported an elegant domino reactionb etween 3-(2-iodophenyl)-1H-indoles and tethered bromoalkyl alkynes for the concise assembly of pentacyclic products 85, which contained an interesting spiroindolenine motif (Scheme 23 d). [54] In addition, the group of Lautens discovered that, in the absence of an adjacent heteroaryl or benzyl group on aryl iodide substrates, vinylpalladiums pecies 81 underwent furtherc arbopalladation of NBE to afford sterically crowded tetrasubstituted helical alkenes 86 through CÀHf unctionalization on the adjacent aromaticr ing (Scheme 23 e). [55] In this case, NBE not only acted as the mediator, but also becamea part of the products.M ore interestingly,i fe nantiopure 80 was applied, an intriguing threefold stereoselectivity was observed in the process:r etention of the central chirality,i nduction of helical chirality (5:1-6.7:1 d.r.…”
Section: Scheme22 Intramolecular Dialkylations/intermolecular Terminmentioning
confidence: 99%
“…In 2000, the Lautens group reported a Pd/NBE catalyzed annulation reaction utilizing aryl iodide and olefin-tethered alkyl halides which functioned as both electrophile (C–X) and nucleophile (alkenyl in intramolecular Heck reaction) (b, Scheme ). Subsequently, alkyl halides tethered to alkyne, amine, propenol, heteroarenes, or ketones were successfully applied to efficiently construct various benzocyclic molecules (b, Scheme ). In addition, epoxides and aziridines were also employed as difunctional reagents through S N 2 type ring opening to synthesize dihydrobenzofurans and indolines (c, Scheme ).…”
mentioning
confidence: 99%
“…Thee xperimental results showed that the phenyl substituent on the alkyne terminus of 2a could be replaced with diversified aryls bearing an electron-donating methoxy group (2b), an EWG such as afluoro (2c), chloro (2d), ester (2e), and nitro (2f)group,oraheterocyclic group such as N-Ts-3-indolyl (2g)and 2-thienyl (2h), and the desired products 3a' '-g' ' were obtained in 63-85 %yields.Notably,the substrate 2i,b earing av inylic substituent, behaved quite well to give 3h' ' in 90 %y ield. [16] Finally,i ti sw orth mentioning that the tether for linking the alkyl bromide and alkyne fragments could be extended with either one more carbon, oxygen, or nitrogen atom, thus enabling the rapid construction of three types of unprecedented pentacyclic frameworks (3r' '-t' ')b earing aseven-membered carbo-or heterocyclic ring unit. Upon treatment with TBAF, 3l' ' underwent TBS removal followed by stereospecific alkoxide addition to furnish af ascinating hexacyclic framework 6.…”
mentioning
confidence: 99%
“…The relative stereochemistry of 3q' ' major was confirmed by X-ray studies. [16] Finally,i ti sw orth mentioning that the tether for linking the alkyl bromide and alkyne fragments could be extended with either one more carbon, oxygen, or nitrogen atom, thus enabling the rapid construction of three types of unprecedented pentacyclic frameworks (3r' '-t' ')b earing aseven-membered carbo-or heterocyclic ring unit.…”
mentioning
confidence: 99%